Combination of Home Care Pharmacy Approach and Nurse’s Health Action Process Approach on Self Care Management and Self Efficacy in Elderly With Hypertension - Linda Juwita; Ninda Ayu Prabasari; Restry Sinansari (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: There are still many hypertensive patients with uncontrolled hypertension and experiencing barriers to self-care. This study attempts to increase motivation and intention in self-care management and self-efficacy through the implementation combination of home pharmacy care approach and Health Action Process Approach (HAPA). This study aimed to know the combination of the Home Care Pharmacy Approach and Nurse's HAPA on self-care management and self-efficacy in the elderly with hypertension. Methods: It was a pre-experimental study that used one group pretest post-test design approach with the population, 60 people. Inclusion criteria were respondents with average blood pressure ≥140/90 mmHg for two measurements. The sampling used a purposive sampling technique. The independent variable was the HAPA and Home Care Pharmacy. The dependent variable is self-care management and self-efficacy. Study instruments are questionnaire self-efficacy, self-care management, standard operating procedures, and HAPA Home Care Pharmacy. Data were analyzed by using paired t-test and Wilcoxon Sign Rank Test with significance paired α ≤ 0.05. Results: Statistical paired t-test showed there was an increase in self-care management (p = 0.006). Statistical Wilcoxon Sign Rank Test showed there was no influence on the home pharmacy care approach and HAPA on self-efficacy (p=0.753). Conclusions: It could be concluded that the implementation of collaboration in-home pharmacy care approach and HAPA improves self-care management. However, these interventions do not affect increasing self-efficacy. The excellent collaboration between healthcare providers will help patients maintain good health during treatment.